A review of extraction technology for carotenoids and vitamin e recovery from palm oil - Abd Manan, Zainuddin (2010)
Carotenoids and vitamin E (tocopherols, tocotrienols) are among the 1% minor valuable components in crude palm oil (Elaeis guineensis). These components have different nutritional functions and benefits to human health. Various technologies have been developed in order to recover these components from being destroyed in commercial refining of palm oil. These include saponification, selective solvent extraction, transesterification followed by molecular distillation and further purification by adsorption using synthetic resins, silica gel and reverse phase CI 8 silica, adsorption chromatography and membrane technology. Even though there are different technologies, but there is one same feature which is the use of solvent. Solvent plays an important role inmost of the technologies. It can be used either as a pre-extraction solvent, main solvent or co-solvent. The problem of most solvents which are used nowadays is that they possess potential fire health and environmental hazards. Due to this, legislation is increasingly restricting the use of certain solvent chemicals. Hence, selection of the most safe, environmentally friendly and cost effective solvent is very important prior to design of alternative extraction methods. Chemical molecular product design is one of the methods that are becoming more popular nowadays for finding solvent with the desired properties prior to experimental testing. © 2010 Asian Network for Scientific Information.